No easy day : the only first-hand account of the Navy SEAL mission that killed Osama Bin Laden /: the only first-hand account of the Navy SEAL mission that killed Osama Bin Laden. (2013) - Owen, Mark, 1976?; Maurer, Kevin
No abstract available